In-vivo expansion of autologous limbal stem cell using simple limbal epithelial transplantation for treatment of limbal stem cell deficiency - Lal, Ikeda (BMJ Publishing Group, 2013)
A 20-year-old man from Bangladesh suffered accidental alkali injury to his right eye in May 2010 leading to total limbal stem cell deficiency. An amniotic membrane graft was performed 5 days after the accident and the patient presented to our institute 6 months later. On ocular examination, his best corrected visual acuity (BCVA) was 20/50 with a 360° pannus at the periphery and central area was spared but had stromal scarring. He underwent simple limbal epithelial transplantation (SLET) taking a limbal biopsy from his left eye and was prescribed steroid and antibiotic eye drops postoperatively as per the standard regimen. At 2 year follow-up, the patient's ocular surface is stable with improvement in  BCVA to 20/25 post-SLET.